Use of control chart in the evaluation of garlic (Allium sativum) for industrial processing - Teodoro, Rafael Marques; Soares, Augusto Martins; Dutra, Mariana Borges de Lima; Morais, Veronica Soares de Paula (Seven Editora, 2023)
Garlic is a horticultural plant of excellent spice, nutritional and herbal value. The conditions to which vegetables are subjected in minimal processing can result in a series of important physiological changes, caused by mechanical damage suffered in the transformation steps. The control chart or chart is a statistical quality tool, which aims to identify deviations and point out possible failures in the production process. Therefore, the work aimed to implement control charts in a company that produces garlic paste. Analyses of the colorimetric parameters L, *a and *b, pH, moisture and ash were made for 20 samples of crushed garlic paste, where it was stored in drums, then 20 grams of garlic paste were collected in 10 different points of each drum. The graphs were assembled with the determined control limits and the results obtained were analyzed. For all analyses the processes were under control, were predictable and stable, except for the colorimetric parameter *a, where a sample exceeded the determined control limit making the process out of control. DOI:https://doi.org/10.56238/alookdevelopv1-178